2023
DOI: 10.1039/d3dt02037a
|View full text |Cite
|
Sign up to set email alerts
|

Fine-tuning the cytotoxicity of ruthenium(ii) arene compounds to enhance selectivity against breast cancers

Sarah A. P. Pereira,
Jan Romano-deGea,
Ana Isabel Barbosa
et al.

Abstract: Ruthenium-based complexes have been suggested as promising anticancer drugs exhibiting reduced general toxicity compared to platinum-based drugs. In particular, Ru(η6- arene)(PTA)Cl2 (PTA = 1,3,5-triaza-7-phosphaadamantane), or RAPTA, complexes have demonstrated efficacy...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…Preliminary data in the literature suggest that ruthenium compounds might be good candidate agents against cancer cells. [26][27][28][29] Studies over the year suggested that ruthenium has anticancer activity against various cancer cells including breast, 30 lung, 31 prostate, and ovarian cells. 13 In this study, eight different novel ruthenium complexes were synthesized and their anticancer potential against MCF-7 cells was studied.…”
Section: Pharmacology/biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary data in the literature suggest that ruthenium compounds might be good candidate agents against cancer cells. [26][27][28][29] Studies over the year suggested that ruthenium has anticancer activity against various cancer cells including breast, 30 lung, 31 prostate, and ovarian cells. 13 In this study, eight different novel ruthenium complexes were synthesized and their anticancer potential against MCF-7 cells was studied.…”
Section: Pharmacology/biologymentioning
confidence: 99%
“…Pereira et al have, in their comprehensive research with RAPTA complexes in the MCF-7 cell line, established that cationic complexes manifest enhanced cytotoxic activity when contrasted with neutral complexes. 28 In our study, apart from the cationic nature of the complex, we also elucidate the influence of solubility. Khan et al designed a series of three half-sandwich Ru(II) arene chloride complexes and conducted a cytotoxicity assessment across concentrations of 0.1, 1, 10, and 100 μM in MCF-7 cells.…”
Section: Pharmacology/biologymentioning
confidence: 99%